2023
DOI: 10.1021/acsanm.2c05066
|View full text |Cite
|
Sign up to set email alerts
|

Highly Crystalline Nanosized NaTaO3/NiO Heterojunctions Engineered by Double-Nozzle Flame Spray Pyrolysis for Solar-to-H2 Conversion: Toward Industrial-Scale Synthesis

Abstract: Sodium tantalate, NaTaO 3 , nanomaterials are highly potent photocatalysts for hydrogen production from H 2 O. Proper interfacing of nano-NaTaO 3 with finely dispersed nano-NiO can produce an n−p type-II heterojunction {NaTaO 3 /NiO} with superior photocatalytic conversion efficiency. Making such nanomaterials widely applicable requires the establishment of an industrial-scale synthesis method, which would allow at least control of nanosize, composition, crystallinity, and interface. Herein, we have developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…FSP Setups for Engineering of RuO 2 /TiO 2 Nanointerfaces. Two distinct FSP configurations (single-nozzle or double-nozzle) 40,44 were applied (Figure 1): in the singlenozzle-FSP (SN-FSP) configuration, all precursor solutions, i.e., Ti and Ru precursors, were combined in in the same solvent mixture. Using a syringe pump (KDS 100 legacy syringe pump, KDScientific), the liquid precursor solution comprising Ti and Ru atoms was sprayed via a capillary tube, at a rate of P = 5 mL min 1 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…FSP Setups for Engineering of RuO 2 /TiO 2 Nanointerfaces. Two distinct FSP configurations (single-nozzle or double-nozzle) 40,44 were applied (Figure 1): in the singlenozzle-FSP (SN-FSP) configuration, all precursor solutions, i.e., Ti and Ru precursors, were combined in in the same solvent mixture. Using a syringe pump (KDS 100 legacy syringe pump, KDScientific), the liquid precursor solution comprising Ti and Ru atoms was sprayed via a capillary tube, at a rate of P = 5 mL min 1 .…”
Section: Methodsmentioning
confidence: 99%
“…In the DN-FSP configuration, TiO 2 and RuO 2 nanoparticles were formed separately using two FSP nozzles, code-named Nozzle-1 and Nozzle-2, respectively (refer to Figure D). After a series of optimizations, ,, an asymmetrical DN-FSP setup was employed (see Figure B,D), where the two nozzles were arranged at specific intersection distances and angles. Specifically, Nozzle-2, dedicated to the synthesis of RuO 2 , was positioned at an angle of β = 30° and a distance of 64 cm from the particle-collection glass-fiber filter.…”
Section: Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, flame spray pyrolysis (FSP) is a versatile technology for the engineering of multifunctional nanostructures and nanodevices [ 20 ] with controllable characteristics (size, phase, crystallinity), and can provide nanoparticles at large quantities. Recently, we have demonstrated that FSP can be successfully employed to synthesize highly-photoactive perovskite materials, e.g., BiFeO 3 [ 21 ], NaTaO 3 [ 22 ]. Herein, we show that FSP-made SrTiO 3 with controlled Vos is a novel approach towards enhanced photoactivity.…”
Section: Introductionmentioning
confidence: 99%